Study on the Nonlinear Damage Creep Model of the Weak Interlayer - Erjian Wei; Bin Hu; Kunyun Tian; Peishan Cen; Zhen Zhang; Zeqi Wang; Shuxiang Chang (Advances in Civil Engineering)
The weak interlayer has become a weak link in slope engineering due to its rheological effect. It is of great significance to study the nonlinear creep model of weak interlayer for long-term stability of the slope. In this paper, based on the creep curve characteristics of weak interlayer and considering the influence of aging damage, the nonlinear improvement of a classical viscoplastic body under stress and time-double threshold conditions is carried out, so that it can more accurately reflect the accelerated creep characteristics of the weak interlayer. By analyzing the relationship between failure load and time, the accelerated creep time threshold of the weak interlayer is obtained. On this basis, a nonlinear damage creep constitutive model of the weak interlayer is constructed and its creep equation is derived. By using the self-defined function fitting tool of Origin software and the Levenberg–Marquardt optimization algorithm, the creep test data of weak interlayer are fitted and compared. The fitting curve is in good agreement with the test data, which shows the rationality and applicability of the nonlinear creep model. The results show that the nonlinear damage creep model constructed in this paper can well describe the creep characteristics of the weak interlayer and the model has important theoretical reference significance for the study of long-term stability of slope with the weak interlayer.